Pemikiran Ibn Rusyd Tentang Wadiah Dalam Kitab Bidayatul Mujtahid - Andika, Musa; Nufus, Najwan; Fadilah, Alfi Nur (Program Studi Hukum Ekonomi Syariah, 2022)
Ibn Rushd was a Maliki cleric who lived in Andalusia (now Spain). This scholar who is known for his progressive philosophical thinking has books of comparative fiqh, four schools in particular. It describes various themes ranging from worship and muamalah. One of the topics studied in this paper is Ibn Rushd's thoughts on wadiah. Where according to Ibn Rushd Wadiah is a muamalah transaction related to material things. Therefore, globally, according to all scholars, it is obligatory for him to take care of entrusted goods from conditions that are normally guarded by human assets. So something that has been clearly assessed as a safeguard is allowed, while it is not clear that it is a safeguard then it is disputed, such as their dispute in the Malik school of thought regarding a person who puts a deposit in his pocket and then it is lost. According to the well-known opinion that the person should be held accountable.